Calculating corporate default risk: zombie firm model / Rika Hiphanna and Zuliani Dalimunthe - Hiphanna, Rika; Dalimunthe, Zuliani (Universiti Teknologi MARA, Selangor, 2022)
As the number of zombie firms has increased globally, investors need to be able to identify these companies since its meet all the terminology of firms that indicated they have a high risk of bankruptcy. With the availability of other default risk models that are already commonly used, the use of zombie firm model identification has not yet been widely implemented as an alternative. This paper analyses whether zombie firm model can give a consistent result compare other existing models to predict default risk such as Altman Z-Score or Merton Naïve Distance to Default Models, by using financial data and daily closing trading price of companies that exist and still traded in Indonesian Stock Exchange for period 2011 - 2020 except for financial sector. For final analysis, we do Wilcoxon Rank test to find tendency of zombie firm existence over the years.